2012
DOI: 10.1039/c2cc16119b
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic ZnO plate twin-crystals periodical arrays

Abstract: We report a periodically patterned organization of hierarchical ZnO twin-crystals on a planar substrate in a biomimetic solution process. The deposition of the porous complex ZnO structure on specific sites of the substrate is achieved by introduction of the substrate surface modification and gelatin in a hydrothermal crystallization of ZnO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 28 publications
0
19
0
Order By: Relevance
“…[11] They further showed that the ZnO hexagons can be deposited on a surface-patterned substrate in an orientated fashion. [12] Greer et al studied in great detail the formation mechanism of the twin-plate mesocrystals. [13] Because of the high surface area and surface selection, mesocrystalline forms of ZnO would be highly interesting as catalyst supports in view of the fact that ZnO is also active in CO 2 activation [14] and CO hydrogenation.…”
Section: Introductionmentioning
confidence: 99%
“…[11] They further showed that the ZnO hexagons can be deposited on a surface-patterned substrate in an orientated fashion. [12] Greer et al studied in great detail the formation mechanism of the twin-plate mesocrystals. [13] Because of the high surface area and surface selection, mesocrystalline forms of ZnO would be highly interesting as catalyst supports in view of the fact that ZnO is also active in CO 2 activation [14] and CO hydrogenation.…”
Section: Introductionmentioning
confidence: 99%
“…The detailed growth mechanism of twin‐plate‐shaped zinc oxide has been discussed in Refs. , while the respective mechanism for growth of spherical particles is described in Refs. .…”
Section: Resultsmentioning
confidence: 99%
“…The properties of micro‐ and nanostructured zinc oxide can be affected via control of size and shape . Therefore, a variety of different crystal shapes has been synthesized, ranging from rods/tubes , belts , spheres , to more complex ones like urchins , flowers , twin‐plates , and pine trees .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11] In the third group are natural organic compounds, for example biopolymers. [12][13][14][15][16][17] Spherical ZnO nanoparticles of narrow size distribution were synthesized in the presence of carboxylic curdlan (Cc), a versitale β-1,3-polyglucuronic acid derivative. The obtained Cc-ZnO nanoparticles showed a good ability of binding proteins.…”
Section: Introductionmentioning
confidence: 99%